Ecological Conversion as a Legal Construction of Environmental Management Based on Dayak Kanayat’n Customary Law - Agustinus Astono; Absori Absori; Kelik Wardiono; Achmadi Achmadi; Nozimbek Dilboboev (Legality : Jurnal Ilmiah Hukum, 2026)
This study investigates the practice of Munuh Adat in Dayak Kanayat’n customary law as the representation of ecological conversion and how this concept can be constructed as environmental management law. This study aims to describe the practice of Munuh Adat and formulate ecological conversion as a legal construct. Using a philosophical approach and a normative legal research method, data were analysed using a qualitative-interpretive technique. The findings indicate that documented cases of Munuh Adat in environmental matters, as reflected in Articles 80 and 81 of the Dayak Kanayat’n Customary Deliberation, represent ecological conversion through mechanisms of acknowledgment of wrongdoing, accountability of the perpetrator, ecological restoration, and cosmological reconciliation between humans, nature, and Jubata’ (God), leaving environmental violations understood as both material losses and disturbances to the balance of life that require overarching restoration. Ecological conversion can therefore be constructed as a legal concept of environmental management because it possesses normative, restorative, communal, and transcendental characteristics, along with legal system components comprising foundational values, legal subjects, protected objects, accountability mechanisms, and restoration-oriented objectives. This construction offers an alternative paradigm for the development of Indonesian environmental law that is more restorative and oriented toward ecological sustainability. This study contributes to the development of environmental law by reconstructing ecological conversion as a legal concept of environmental management established in Dayak Kanayat’n customary law, thereby extending environmental law beyond the positivist paradigm.